The Role of Tbx20 in Cardiovascular Development and Function - Chen, Yuwen; Xiao, Deyong; Zhang, Lu; Cai, Chen-Leng; Li, Bai-Yan; Liu, Ying (Frontiers in Cell and Developmental Biology, 2021)
Tbx20 is a member of the Tbx1 subfamily of T-box-containing genes and is known to play a variety of fundamental roles in cardiovascular development and homeostasis as well as cardiac remodeling in response to pathophysiological stresses. Mutations in TBX20 are widely associated with the complex spectrum of congenital heart defects (CHDs) in humans, which includes defects in chamber septation, chamber growth, and valvulogenesis. In addition, genetic variants of TBX20 have been found to be associated with dilated cardiomyopathy and heart arrhythmia. This broad spectrum of cardiac morphogenetic and functional defects is likely due to its broad expression pattern in multiple cardiogenic cell lineages and its critical regulation of transcriptional networks during cardiac development. In this review, we summarize recent findings in our general understanding of the role of Tbx20 in regulating several important aspects of cardiac development and homeostasis and heart function.